Choroidal Vascular Impairment in Intermediate Age-Related Macular Degeneration - Flores, Rita (2022)
Funding: This work was supported by Fundação para a Ciência e Tecnologia project PTDC/MEDPAT/30385/2017 and iNOVA4Health-UIDB/04462/2020, a program financially supported by Fundação para a Ciência e Tecnologia (FCT) / Ministério da Educação e Ciência, Portugal, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement. A.C.F. was funded by FCT PhD studentship (PD/BD/135503/2018).